MSME Financial Management: Cash Flow Management Strategies to Enhance Business Sustainability - Supriyanto; Damanik, Septa Damewanti; Prasetyo, Ginanjar; Alie, Maria Septijantini; Oktaria, Eka Travilta (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to identify effective cash-flow management strategies for Micro, Small, and Medium Enterprises (MSMEs) in Bandar Lampung, Indonesia. Although MSMEs play a critical role in national economic development, many still experience liquidity problems due to weak financial recording, the mixing of personal and business funds, and the limited use of digital financial tools. This research employs a descriptive qualitative approach, collecting data through in-depth interviews, observations, and documentation involving 15 MSMEs from the culinary and retail sectors. The findings reveal that cash-flow management can be significantly improved through four key strategies: monthly budgeting, daily transaction recording, structured management of receivables and payables, and the use of digital financial applications. These strategies enhance financial control, strengthen preparedness for unexpected expenses, and support more informed business decision-making. The study highlights the importance of financial and digital literacy for MSMEs and calls for continued government support through training and capacity-building programs.   Kata Kunci : UMKM, manajemen keuangan, arus kas, strategi, kelangsungan usaha.